(untitled) (Journal of Dhaka Medical College, 2016)
Eclampsia is a major cause of maternal morbidity and mortality. It is largely a preventable disease provided the pregnant women get regular antenatal care. Its incidence in Bangladesh is still high. Lack of health education, low socioeconomic condition, lack of adequate facilities to deal with the emergency situation, inadequate referral and transfer system are important contributing factors of consideration. In many peripheral centers, facilities to deal with such a complicated patient are absent. This prospective study was conducted in the eclampsia ward in the Department of Obstetrics and Gynaecology, Dhaka Medical College Hospital, Dhaka, from July to December, 2004. Our aim was to identify the better mode of termination of pregnancy in eclamptic patients. Hundred antenatal eclamptic patients were purposively selected for the study. Eclampsia is a disease of relatively younger age group. Out of 100 patients, 53 percent were < 20 years of age, 42 percent patients were primigravida and 67 percent patients were from low socioeconomic condition. 72 percent patients of vaginal delivery group and 60 percent patients of caesarean section group had no antenatal care (ANC). Maternal morbidity was more in vaginal delivery group (56%) than in caesarean section group (36%). Maternal mortality rate was 4% in both the groups. Perinatal mortality was higher in vaginal delivery (36%) than in caesarean section group (22%). J Dhaka Medical College, Vol. 24, No.2, October, 2015, Page 92-98